Analysis of the geographical distribution of terrorist operations in Iraq for the period 2003-2018 - Al-Nashi, Thaer Ghalib Mezyad; Al-Kaabi, Ali AbdulAmir Sajit (Al-Adab Journal, 2021)
The study showed that the volume of terrorist operations in Iraq reached (26165) operations that varied in their geographical distribution among the governorates of Iraq, and it became clear that the concentration of terrorist operations was most intense in the governorate of Baghdad, as the volume of operations in it reached (7854) operations, with relative importance (30%), while The size of its population reached (8,126,755) with a relative importance (21.3%) of the Iraqi population for the year 2018. While the lowest volume of terrorist operations during the study period was recorded in 2003, it reached (102) operations of relative importance (0.04%), while the largest volume was recorded. In 2014, (3931) terrorist attacks were of relative importance (15%).The study also showed the emergence of a high range of terrorist operations surrounding the capital, Baghdad, in the governorates that are characterized by a diverse population composition in the governorates (Baghdad, Diyala, Salah al-Din, Nineveh, and Kirkuk). And by analyzing the neighborhood relationship to find out the pattern of the distribution of terrorist operations in Iraq, it was found that the value of the nearest neighbor is (0.46) and this means that the distribution is unevenly aggregated and it became clear through the oval that the direction of the geographical distribution of terrorist operations in Iraq extends in a northwest-southeast direction that includes all the area of ​​the governorate. Baghdad, most of Salah al-Din Governorate, Diyala Governorate, areas east of Anbar Governorate, south and southeast Nineveh Governorate, and eastern Kirkuk governorate.